2005
DOI: 10.1038/oby.2005.137
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortisol Bioavailability, Abdominal Obesity, and the Metabolic Syndrome in Obese Women

Abstract: DUCLOS, MARTINE, PATRICIA MARQUEZ PEREIRA, PASCAL BARAT, BLANDIN GATTA, AND PATRICK ROGER. Increased cortisol bioavailability, abdominal obesity, and the metabolic syndrome in obese women. Obes Res. 2005;13:1157-1166. Objective: This study was conducted to obtain a detailed profile of hypothalamo-pituitary-adrenal (HPA) axis activity and reactivity and its differential relationships with body fat distribution and total fat mass in premenopausal obese women. Research Methods and Procedures:Cortisol responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 42 publications
(53 reference statements)
7
106
1
5
Order By: Relevance
“…Finally, a slightly different result emerged in a sample of obese women, where those with an abdominal body fat distribution (WHR > 0.85) had a similar CAR as those with a peripheral body fat distribution (WHR < 0.85). However, the actual salivary cortisol values were significantly lower at each time point among those with an abdominal body fat distribution (Duclos et al, 2005) Conversely, 3 studies found evidence in support of the opposite perturbation in CAR -an exaggerated response. One study, for example, found that CAR correlated positively with BMI, WHR, and sagittal diameter in men (Wallerius et al, 2003).…”
Section: Cortisol Awakening Response (Car)mentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, a slightly different result emerged in a sample of obese women, where those with an abdominal body fat distribution (WHR > 0.85) had a similar CAR as those with a peripheral body fat distribution (WHR < 0.85). However, the actual salivary cortisol values were significantly lower at each time point among those with an abdominal body fat distribution (Duclos et al, 2005) Conversely, 3 studies found evidence in support of the opposite perturbation in CAR -an exaggerated response. One study, for example, found that CAR correlated positively with BMI, WHR, and sagittal diameter in men (Wallerius et al, 2003).…”
Section: Cortisol Awakening Response (Car)mentioning
confidence: 91%
“…After a 0.0035 mg per kilogram body weight dose of dexamethasone, another sample of obese females did not differ from non-obese females in serum cortisol levels (Rask et al, 2002). Another sample of only females found that those with a WHR > 0.85 did not differ in feedback sensitivity, as indexed through plasma, from those with a WHR < 0.85 in response to a 0.25 mg dose of dexamethasone (Duclos et al, 2005). Finally, a study of both obese and normal BMI males and females found sex differences wherein obese females demonstrated significantly lower inhibition after dexamethasone doses of 0.0035 mg, 0.0070 mg, and 0.015 mg per kilogram of body weight, but that there were no differences in between obese and non-obese males (Pasquali et al, 2002).…”
Section: Glucocorticoid Feedback Sensitivity -Dexamethasone Suppressimentioning
confidence: 92%
See 2 more Smart Citations
“…Wang, 2011). It has been demonstrated that circulating cortisol concentrations are higher in patients with MetSyn compared with healthy subjects, both in basal conditions and during dynamic stimulation (Duclos et al, 2005;Misra et al, 2008;Phillips et al, 1998;Sen et al, 2008;Weigensberg et al, 2008). Furthermore, increased 11 -HSD1 activity in VAT may generate increased cortisol levels within AT and liver and thereby promote features of the MetSyn (Walker & Andrew, 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%